Accuracy of self‐reported birth outcomes relative to birth certificate data in an Internet‐based prospective cohort study. Issue 5 (6th May 2021) - Wise, Lauren A.; Wang, Tanran R.; Wesselink, Amelia K.; Willis, Sydney K.; Chaiyasarikul, Alina; Levinson, Jessica S.; Rothman, Kenneth J.; Hatch, Elizabeth E.; Savitz, David A.
Abstract: Background: The accuracy of birth outcome data provided by Internet‐based cohort study participants has not been well studied. Methods: We compared self‐reported data on birth characteristics in Pregnancy Study Online (PRESTO), an Internet‐based prospective cohort study of North American pregnancy planners, with birth certificate data. At enrolment, participants were aged 21‐45 years, attempting conception, and not using fertility treatment. Women completed online questionnaires during preconception, early and late pregnancy, and postpartum. We requested birth certificate data during 2014‐2019 from seven health departments in states with the most participants. After restricting to singleton births, we assessed specificity, sensitivity, and agreement comparing self‐reported data from postpartum questionnaires with birth certificate data for gestational age at delivery (GA) and birthweight (grams). Our primary measure of self‐reported GA (weeks) was calculated as [280‐(due date‐birth date)]/7. We used log‐binomial regression to assess predictors of agreement. Results: We linked 85% (771/909) of women in selected states. Median age of women was 30 years (range: 21‐42), 84% had ≥ 16 years of education, nearly 96% were married, 12% had household incomes <$50 000, 32% were parous, and 85% identified as non‐Hispanic White. Median recall interval was 6 months. Among those with self‐reported data, 89% reported the same GA as the birth certificate and 98% reported GA within 1 week of the birth certificate. Self‐report of preterm birth (GA < 37 weeks) agreed with information from birth certificates for 100% of women; sensitivity was 100%, and specificity was 99%. Self‐reported low birthweight (<2500 grams) agreed with birth certificates for 93% of women; sensitivity and specificity were 93% and ≥99%, respectively. Predictors of poorer agreement included higher parity and longer pregnancy attempt time for GA, and lower education and longer recall interval for birthweight. Conclusion: Self‐reported data on GA and birthweight from an Internet‐based cohort showed high accuracy compared with birth certificates.